Flocs vs granules : differentiation by fractal dimension - Bellouti, M. (1997)
High rate anaerobic wastewater treatment systems usually give rise to biomass structured in different types of aggregates, depending on prevalent environmental conditions. Although highly dependent on wastewater characteristics, granules are generally formed and found in UASB reactors, whereas flocs are mainly found in fixed bed reactors. Different structures usually have different shapes and surface roughness. The aim of this work is to provide a contribution to the differentiation of those kinds of aggregates. A numerical parameter, the fractal dimension, was used to quantify the surface roughness. The fractal dimension, of two families of particles, was measured by two methods: (i) a box counting method; (ii) a method based on an area-size relationship. In both cases, the differences were highly statistically significant. Using the box counting method, for each of the 54 particles of each family, the average fractal dimension was 1.90 ± 0.02 for flocs and 1.95 ± 0.01 for granules (±99% confidence interval). The log-log plot of area vs longest size was linear and the calculated fractal dimensions from this plot were 1.84 ± 0.13 and 2.14 ± 0.08 (±99% confidence interval) for flocs and granules, respectively. Fractal dimension was proven to be a suitable parameter to quantify and differentiate surface roughness of different microbial aggregates present in high rate anaerobic digesters.